The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/15548627.2016.1164357
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine kinase receptor EGFR regulates the switch in cancer cells between cell survival and cell death induced by autophagy in hypoxia

Abstract: (2016) Tyrosine kinase receptor EGFR regulates the switch in cancer cells between cell survival and cell death induced by autophagy in hypoxia, Autophagy, 12:6, 1029-1046, DOI: 10.1080/15548627.2016 ABSTRACTAutophagy is an intracellular lysosomal degradation pathway where its primary function is to allow cells to survive under stressful conditions. Autophagy is, however, a double-edge sword that can either promote cell survival or cell death. In cancer, hypoxic regions contribute to poor prognosis due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 78 publications
4
88
0
Order By: Relevance
“…The universally positive role of autophagy in CSC maintenance is, however, at odds with a report demonstrating that autophagy deficiency stabilizes the transcription factor TWIST1, promotes EMT in vitro , and tumor growth and metastasis using a A431 squamous cell carcinoma xenograft mouse model [60, 61]. Most importantly, in several cancer cell types, including breast cancer, EGFR activation suppresses autophagy [13, 20, 21]. Thus, EGFR inhibition should lead to an increase, rather than a decrease, in autophagy [22, 23], and the role of autophagy in EGFR-mediated regulation of breast CSCs needs further clarification.…”
Section: Discussionmentioning
confidence: 99%
“…The universally positive role of autophagy in CSC maintenance is, however, at odds with a report demonstrating that autophagy deficiency stabilizes the transcription factor TWIST1, promotes EMT in vitro , and tumor growth and metastasis using a A431 squamous cell carcinoma xenograft mouse model [60, 61]. Most importantly, in several cancer cell types, including breast cancer, EGFR activation suppresses autophagy [13, 20, 21]. Thus, EGFR inhibition should lead to an increase, rather than a decrease, in autophagy [22, 23], and the role of autophagy in EGFR-mediated regulation of breast CSCs needs further clarification.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the development of human diseases, autophagy has been shown to be a double-edged sword. In some cases, autophagy is a cytoprotective mechanism, but in others, autophagy is a pro-death response to stresses, especially chemotherapy at the cellular and organic levels (8,9). Many autophagy-related genes (Atgs) have been implicated in controlling these complicated behaviors during autophagy, and approximately half of them are evolutionarily conserved from yeast to human (10).…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy has been previously implicated in the release of proteins through atypical pathways [47][48][49][50][51] and several studies have linked degradation of Cav1 to autophagy [52][53][54][55] . Our EM studies demonstrated abundant small vesicles positive for Cav1 in the cytoplasm of expressing cells.…”
Section: Autophagy Is Critical For the Release Of Cav1 From Lncap Cellsmentioning
confidence: 99%